Optimization of the Shortest Tsunami Evacuation Route Using Djikstra’s Algorithm in Benoa Village - Ida Bagus Kade Puja Arimbawa K; Wayan Sukartiasih; Agung Sedayu (Brilliance: Research of Artificial Intelligence, 2023)
Benoa Village has an area of approximately 2.38 km² and a population of 9,569 people in 2020 with a population density of 4,013 people/km2. This area is included in the list of tsunami-prone areas because the area is located on the edge of the Indian Ocean, which is known as an area with a high level of earthquake and volcanic activity. The 2004 tsunami that hit the coast of the Indian Ocean increased the potential for similar disasters to occur in the area. Determination of the shortest evacuation route in Benoa Village using Djikstra Algorithm. The result obtained is a path from the evacuation starting point vertex to the comfort zone node. Thisvertex represents places and road intersections arranged in the form of a weighted graph (distance) with a total of 51 vertexs, and an Adjacency Matrix is formed which is processed using the C++ Program. The Safe Zone vertex (Grand Hyatt Bali Temporary Meet Point (V50), Hattrick Futsal (V51)) are headed from the evacuation starting point of Serangan Beach (4.49km to V50, 6.94km to V51), Noanui Beach (3.95km to V50, 6.39km to V51), Samuh Beach (2.75km to V50, 5, 19km to V51), Nusa Dua Beach A (3.54km to V50, 5.48km to V51), Nusa Dua Beach B (3.47km to V50, 4.79km to V51), Peninsula Island (4.69km to V50, 4.80km to V51), Megiat Beach (4.81km to V50, 4.15km to V51) and Geger Beach (5.86km to V50, 5.09km to V51).